Caring for National Unity: Lessons from the Youth Pledge to Today - Ramadani, Tifla; Assingkily, Maiyatul Jannah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This article discusses the importance of maintaining the unity of the indonesian nation through lessons learned from the youth pladge declared in 1928. Using a literature study method, this article finds that the spirit of unitycontained in the Youth Pladge is very relevant in facing socio-cutural challenges in the modern era. The results of the ana;yss show that the application of the values of the Youth Pledge can strengthen the sene of nationality and unity in society. The conclusion of this study emphasizes the need for a joint commitment to maintaining unity for a better future for the nation.